Ground reaction force during the Upper Quarter Y-Balance Test - Degot, M.; Rogowski, I.; Blache, Y. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Originally proposed for pre-season screening in elite athletes, the Upper Quarter Y-Balance Test (UQYBT) is a physical performance test increasingly used by trainers and clinicians, believed to investigate shoulder functions like stability, mobility, proprioception or strength (Bullock et al. 2017). While the participant stands in one-handed push up position, the other hand has to reach maximal distance in medial, inferolateral and superolateral directions. Main outcomes measures of UQYBT are distances, composites distances and score, which have been validated statistically (Westrick et al. 2012; Degot, Blache, Neyton, et al. 2019). No study has however identified the key neuromuscular features required to achieve the UQYBT performance. In consequence, in-depth analysis of the forces produced by the stance upper limb may contribute to better identify the strategy developed by athletes to reach maximal distances in the three directions.